Intention to visit India among potential travellers: Role of travel motivation, perceived travel risks, and travel constraints. (July 2019) - Khan, Mohammad J; Chelliah, Shankar; Ahmed, Sahrish
Several studies explain the direct effect of travel motivation, perceived risks, and travel constraints on visit intention. However, there are relatively limited investigations on the combined effect of these factors on visit intention. This study empirically tests a comprehensive model of visit intention based on travel motivation, perceived risks, and travel constraints. A quantitative study was performed on 316 university students in Malaysia. The results of the study found that travel motivation had a positive influence on visit intention. For perceived travel risks, performance risk and time risk had negative effects on visit intention. Physical risk, financial risk, and socio-psychological risk did not affect visit intention. Among travel constraints, interpersonal and intrapersonal constraints were negatively related to visit intention. The study also found that the effect size ( f 2 ) of statistically significant relationship was low in a few cases. The findings provide useful insight to destination managers in terms of integrating the influential factors in promotional strategies to develop intentions to visit India among potential market segment. The study also suggested future researchers to test the research framework at different levels of decision-making and contexts to prove its usability.